Mechanical design engineering handbook - Childs, Peter R. N. (Butterworth-Heinemann/Elsevier, 2014)
"Mechanical Design Engineering Handbook is a straight-talking and forward-thinking reference covering the design, specification, selection, use and integration of machine elements fundamental to a wide range of engineering applications. Develop or refresh your mechanical design skills in the areas of bearings, shafts, gears, seals, belts and chains, clutches and brakes, springs, fasteners, pneumatics and hydraulics, amongst other core mechanical elements, and dip in for principles, data and calculations as needed to inform and evaluate your on-the-job decisions. Covering the full spectrum of common mechanical and machine components that act as building blocks in the design of mechanical devices, Mechanical Design Engineering Handbook also includes worked design scenarios and essential background on design methodology to help you get started with a problem and repeat selection processes with successful results time and time again. This practical handbook will make an ideal shelf reference for those working in mechanical design across a variety of industries and a valuable learning resource for advanced students undertaking engineering design modules and projects as part of broader mechanical, aerospace, automotive and manufacturing programs. Clear, concise text explains key component technology, with step-by-step procedures, fully worked design scenarios, component images and cross-sectional line drawings all incorporated for ease of understanding. Provides essential data, equations and interactive ancillaries, including calculation spreadsheets, to inform decision making, design evaluation and incorporation of components into overall designs. Design procedures and methods covered include references to national and international standards where appropriate"--Provided by publisher.